1999
DOI: 10.1590/s0100-83581999000100002
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do armazenamento da calda na eficácia de herbicidas aplicados em pré-emergência (parte II)

Abstract: RESUMO1 Recebido para publicação em 17/03/95 e na forma revisada em 23/12/98. 2 Parte da dissertação do primeiro autor apresentada à FCAVJ/UNESP, Campus de Jaboticabal, para obtenção do título de Mestre em Agronomia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…molecule will be break or degraded (STEWART et al, 2009). For efficiency, two similar studies reported that the mixture of 2,4-D + glyphosate had reduced control of Panicum maximum Jacq., but for two residual herbicides ametrine and diuron, there was no difference in the emergence of weeds (RAMOS & DURIGAN, 1998;RAMOS & DURIGAN, 1999). Also, the use of 2,4-D amine for the control of Taraxacum officinale L. with hard water (400 and 600 ppm CaCO 3 ) was not affected by the storage time but can be negative affected by divalent cations (PATTON et al, 2016;SCHORTGEN & PATTON, 2019).…”
Section: Carrier Water Ph Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…molecule will be break or degraded (STEWART et al, 2009). For efficiency, two similar studies reported that the mixture of 2,4-D + glyphosate had reduced control of Panicum maximum Jacq., but for two residual herbicides ametrine and diuron, there was no difference in the emergence of weeds (RAMOS & DURIGAN, 1998;RAMOS & DURIGAN, 1999). Also, the use of 2,4-D amine for the control of Taraxacum officinale L. with hard water (400 and 600 ppm CaCO 3 ) was not affected by the storage time but can be negative affected by divalent cations (PATTON et al, 2016;SCHORTGEN & PATTON, 2019).…”
Section: Carrier Water Ph Studiesmentioning
confidence: 99%
“…The pH of carrier water for the mixture of pesticides may play a very important role in the processes of degradation, solubility and efficiency (ROSKAMP et al, 2013b;MUDGE et al, 2010;DEVKOTA & JOHNSON, 2019). Thus, water pH can interfere in the efficiency of pesticides, which can also be affected by the time of spray preparation before the application (RAMOS & DURIGAN, 1999). Besides this, there may be an interaction with the aciddissociation constant (pKa), which consists in the pH value at which it causes 50% of dissociation and association of each molecule with the environment (NELSON et al, 2017), which can influence in the absorption and translocation of some herbicides.…”
Section: Introductionmentioning
confidence: 99%
“…Neste sentido, é importante o conhecimento de informações sobre a modificação das propriedades físico-químicas que facilita a incompatibilidade e a rápida degradação destes produtos, que por sua vez pode proporcionar um resultado negativo no controle de plantas daninhas. E ainda determinar os períodos de tempo pelos quais as caldas de herbicidas possam ser armazenadas, sem que haja prejuízo à eficácia dos mesmos e, consequentemente, sem resultar em prejuízos ao agricultor (RAMOS & DURIGAN, 1999).…”
unclassified